Forum - Conservation experiences, evidence, and opinions: Conservation front lines need experienced troops: the role of a scientific trust in a changing world (Avocetta, 2024)
The active participation of scientific trusts, including CISO (Centro Italiano Studi Ornitologici), in applied conservation actions plays a crucial role in addressing the challenges faced by natural and semi-natural landscapes, which are increasingly impacted by improper land-use and land-cover. This is particularly true for those landscapes where Large Infrastructures and Big Events (LIBEs) are planned. In these circumstances, researchers, professionals, and environmentalists typically express their concerns on the impacts of LIBEs through mediatic campaigns, often highlighting the ecological importance of vulnerable areas. These actions form the first, useful level of engagement in conservation. However, we advocate for a more proactive role of scientific trusts, which should entail forming task forces of conservation experts and providing scientific support in management decisions when LIBEs are being considered. In our opinion, scientists should locally produce original field studies by using effective sampling designs such as Before-After-Control-Impact surveys. We highlight that such a targeted level of action may support the public agencies when authorizing (or not) LIBEs, by providing evidence-based information about the ecological value of the target area and the potential impacts of LIBEs on ecosystem functions and local biodiversity. The aim is to avoid emotion-based social media loops, conflicts, and polarizations in the discussions about the ecological impacts of LIBEs.
Keywords: Biodiversity Conservation; Environmental Impact Assessment; Task Force; Big Events; Large Infrastructures